Analysis of the Carrying Capacity of Groundwater Availability and its Relation to Population Growth in Settlements of Colomadu District, Karanganyar Regency - Kusumaningrum, Lia; Karina, Ressa; Fil'ardiani, Nida U; Mardiyanto, Muhammad B; Jabbar, Sa'ad A; Khoirunnisa, Sofiyana; Raharjo, Yaqut Amjat A; Santika, Youhana E; Arta, Yunia P Annisa; Daniswara, Agnar P (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Colomadu District is an area on the outskirts of or around a city that is experiencing rapid development due to the local population’s interest in moving, causing an increase in population. The aim is to determine the projected use of groundwater in Colomadu District, Karanganyar Regency, to determine the use of groundwater needs in each village in Colomadu District, Karanganyar Regency in 2021, and to determine when the balance between supply (availability) and demand of groundwater in Colomadu District will be exceeded or in deficit. The research method used was data collection in the form of sampling, measuring water quality, and interviews. Sampling was carried out by collecting water from the residents' wells and taking as many as two samples per village, which represented the water quality in each village. The samples were collected by first drawing water from the well, then the prepared sample bottles were rinsed three times using sample water (well water), and the rinsed bottles were then filled with sample water. The projection of groundwater use in Colomadu District in 2025 is 3,345,311.68 m3 year-1; in 2030 is 3,716,727.52 m3 year-1; in 2035 is 4,129,380.08 m3 year-1; and in 2040 is 4,587,847.71 m3 year-1. Projections are made until demand exceeds supply, namely, in 2085, when demand can reach 11,833,854.16 m3 year-1 with a population of 272,244 people.